Patient safety culture in nurses' clinical practice - Cláudia Patrícia da Costa Brás; Manuela Maria Conceição Ferreira; Maria do Céu Aguiar Barbieri de Figueiredo; João Carvalho Duarte (Universidade de São Paulo, 2023)
Abstract Objective: to assess the psychometric characteristics of the Hospital Survey on Patient Safety Culture, to characterize the patient safety culture, and to assess the influence of the sociodemographic and professional variables on the safety culture dimensions. Method: a methodological, observational, analytical and cross-sectional study conducted with 360 nurses in which the Hospital Survey on Patient Safety Culture questionnaire was used. The data were submitted to descriptive and inferential analysis, as well as to feasibility and validity studies. Results: the nurses' mean age is 42 years old, their mean time of professional experience is 19 years, and they are mostly female. Good internal consistency was obtained (Cronbach's alpha: 0.83), as well as acceptable model fit quality indices. Teamwork within units, Supervisor expectations and Feedback and communication about errors were the dimensions that obtained scores above 60%. Non-punitive response to error, Frequency of events reported, Support for patient safety and Staffing presented scores below 40%. These dimensions are influenced by age, schooling level and professional experience. Conclusion: the psychometric properties of the questionnaire certify its good quality. Teamwork can be considered as an enhancing factor for the safety culture. Assessing the safety culture allowed identifying problematic dimensions, thus enabling planning of future interventions.